Electroacupuncture Regulates Hippocampal Synaptic Plasticity via miR-134-Mediated LIMK1 Function in Rats with Ischemic Stroke. (2nd January 2017) - Liu, Weilin; Wu, Jie; Huang, Jia; Zhuo, Peiyuan; Lin, Yunjiao; Wang, Lulu; Lin, Ruhui; Chen, Lidian; Tao, Jing
Abstract : MircoRNAs (miRs) have been implicated in learning and memory, by regulating LIM domain kinase (LIMK1) to induce synaptic-dendritic plasticity. The study aimed to investigate whether miRNAs/LIMK1 signaling was involved in electroacupuncture- (EA-) mediated synaptic-dendritic plasticity in a rat model of middle cerebral artery occlusion induced cognitive deficit (MICD). Compared to untreatment or non-acupoint-EA treatment, EA at DU20 and DU24 acupoints could shorten escape latency and increase the frequency of crossing platform in Morris water maze test. T2-weighted imaging showed that the MICD rat brain lesions were located in cortex, hippocampus, corpus striatum, and thalamus regions and injured volumes were reduced after EA. Furthermore, we found that the density of dendritic spine and the number of synapses in the hippocampal CA1 pyramidal cells were obviously reduced at Day 14 after MICD. However, synaptic-dendritic loss could be rescued after EA. Moreover, the synaptic-dendritic plasticity was associated with increases of the total LIMK1 and phospho-LIMK1 levels in hippocampal CA1 region, wherein EA decreased the expression of miR-134, negatively regulating LIMK1 to enhance synaptic-dendritic plasticity. Therefore, miR-134-mediated LIMK1 was involved in EA-induced hippocampal synaptic plasticity, which served as a contributor to improving learning and memory during the recovery stage of ischemic stroke.